Hygrothermal performance of well-insulated wood-frame walls in Baltic climatic conditions - Anatolijs Borodinecs; Vladislavs Jacnevs; Lakatos Ákos; Staņislavs Gendelis (Case Studies in Thermal Engineering)
This study investigates the hygrothermal performance of wood-frame walls in the Baltic region under varying moisture loads, comparing bio-based and conventional insulation materials. The research combines experimental climate chamber testing with DELPHIN simulations to assess moisture risk mitigation, energy efficiency and mould growth resistance. The results highlight that bio-based insulations, such as wood fibre, outperform conventional materials due to higher vapour diffusion resistance (μ = 5) and superior moisture-buffering capacity. For instance, wood fibre insulation reduced the RHT-index by 30.6 % compared to mineral wool while maintaining mould indices below 0.71. Furthermore, the study identifies optimal wind-to-vapour barrier ratios, such as 1:2 for cellulose insulation, that mitigate mould risks in high-moisture conditions. The findings advocate for adopting vapour-open wall assemblies and bio-based materials to enhance building durability, energy efficiency and moisture resilience in cold climates.